IBS as a diverse disease. A comprehensive review - Dylik, Adrianna; Gryczyńska, Weronika; Musiał, Mikołaj; Krawczak, Łukasz; Gulaczyk, Hanna; Spychalski, Jan; Kaczmarek, Mikołaj; Grochowska, Wiktoria; Spychalska, Maria (Journal of Education, Health and Sport, 2025)
Introduction: Irritable Bowel Syndrome is one of the most popular diseases among the gastrointestinal difficulties. The main problem is lower quality of life because of troublesome symptoms of the disease. Aim of the study: This review seeks to consolidate the current understanding of IBS, emphasizing the prevalence of this condition and the persistent challenges in achieving a definitive understanding, even after decades of research. The primary objective is to highlight contemporary approaches to patient care, revisiting both pharmacological and non-pharmacological treatment strategies. Materials and methods: The analysis is based on a thorough review of peer-reviewed literature published between 2020 and 2025, ensuring the inclusion of the most up-to-date insights. Knowledge was sourced from PubMed using the advanced search with terms „irritable bowel syndrome” with „or” and „IBS”, ultimately returning 1,228 results. Results and conclusion: The findings underscore the necessity of a multidisciplinary approach involving a team of specialists to provide comprehensive care. Additionally, a crucial factor is the patient's diet and overall well-being, which play a pivotal role in determining the progression and course of the condition. Furthermore, a clear conclusion has been established that, the psychological dimension—integral to both the disease and its management—emerges as a critical factor that warrants careful consideration and should not be underestimated.